2020
DOI: 10.1111/bph.15083
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin‐3‐O‐glucoside improves non‐alcoholic fatty liver disease by promoting PINK1‐mediated mitophagy in mice

Abstract: Background and Purpose: Identifying safe and effective compounds that target to mitophagy to eliminate impaired mitochondria may be an attractive therapeutic strategy for non-alcoholic fatty liver disease. Here, we investigated the effects of cyanidin-3-O-glucoside (C3G) on non-alcoholic fatty liver disease (NAFLD) and the underlying mechanism. Experimental Approach: Non-alcoholic fatty liver disease was induced by a high-fat diet for 16 weeks. C3G was administered during the last 4 weeks. In vivo, recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 53 publications
(75 reference statements)
2
68
0
Order By: Relevance
“…Activation of Parkin in neurons may also be associated with proximal signalling events independent of mitophagy and interestingly, several of the common neuronal sites we identified, occur on proteins involved in fatty acid oxidation and metabolism in the mitochondria including CPT1α, ACSL1, VDACs, CYB5R3 (Figure 2 and 3). Recently several in vivo physiological studies have suggested a link between fatty acid oxidation and mitophagy mechanisms in non-neuronal tissues (Shao et al, 2020, Li et al, 2020) and in future work it will be interesting to investigate whether Parkin-induced ubiquitylation of these proteins affects fatty acid metabolism at the molecular level in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Parkin in neurons may also be associated with proximal signalling events independent of mitophagy and interestingly, several of the common neuronal sites we identified, occur on proteins involved in fatty acid oxidation and metabolism in the mitochondria including CPT1α, ACSL1, VDACs, CYB5R3 (Figure 2 and 3). Recently several in vivo physiological studies have suggested a link between fatty acid oxidation and mitophagy mechanisms in non-neuronal tissues (Shao et al, 2020, Li et al, 2020) and in future work it will be interesting to investigate whether Parkin-induced ubiquitylation of these proteins affects fatty acid metabolism at the molecular level in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Fat-induced liver damage is associated with inhibited mitophagy and following the mitochondria-mediated death of hepatocytes [ 33 ]. However, this also suggests several potential mitochondrial targets that can be used as a treatment to reduce inflammation via activated mitophagy, or as a prevention therapy to enhance mitophagy and protect against surplus lipid accumulation in the liver [ 34 , 35 ].…”
Section: Considering Nafld/nash As a Mitochondrial Diseasementioning
confidence: 99%
“…And whole-body insulin resistance and hepatic insulin resistance were observed in high-fat diet-fed liver-specific Parkin knockout mice ( Edmunds et al, 2020 ). In high-fat diet-fed mice, cyanidin-3-O-glucoside, a kind of anthocyanins mainly found in black rice, black beans and purple potatoes, significantly reduces body weight by activating PINK1-mediated mitophagy ( Li X. et al, 2020 ). Quercetin is proved to inhibit the body weight gain in high-fat diet-fed mice, simultaneously suppress the level of hepatic or serum cholesterol and triglyceride, and inhibit the expression of lipogenic gene fatty acid synthase (FAS) ( Liu et al, 2018 ).…”
Section: Phytochemical-mediated Mitophagy In Metabolic Disordersmentioning
confidence: 99%